Not Updated Since 2000? A Review of Biodiversity Assessments in Silot Bay, Liloan, Cebu, Philippines - Angulo, Karl Cirilson Ellema (Aquatic Life Sciences, 2026)
Coastal ecosystems support high levels of marine biodiversity and provide essential services, including shoreline protection, carbon sequestration, and fisheries production. Silot Bay, Liloan, Cebu, Philippines, is an ecologically and socio-economically important embayment; however, biodiversity assessments in the area remain sparse and temporally fragmented. This study presents a narrative review with structured literature search elements to synthesize available ecological studies on major taxonomic groups, including mangroves, fish, meiofauna, and algae, and to evaluate methodological consistency among studies retrieved from Google Scholar, ScienceDirect, Philippine E-Journals, and institutional repositories from local universities. A total of nine studies met the inclusion criteria, the majority of which were conducted prior to 2000, with post-2000 research limited to a single study on algal communities. Substantial variation in sampling methods, effort, spatial coverage, and taxonomic resolution constrains direct comparison across studies and limits interpretation of temporal patterns. Differences in reported species richness and community composition are evident across taxa; however, these patterns cannot be confidently attributed to ecological change due to methodological inconsistencies and limited data availability. The small number of studies and reliance on partially inaccessible historical data further restrict the establishment of a reliable biodiversity baseline for Silot Bay. Overall, this review highlights significant knowledge gaps and emphasizes the need for standardized, multi-taxa biodiversity assessments to support long-term monitoring and evidence-based coastal management.